Performances of commercial hybrid broiler in villages of Bangladesh (Bangladesh Veterinarian, 2016)
A total of 20 broiler farms were enumerated to evaluate the production performance of broiler birds and farm management status at rural villages of Mymensingh Sadar (district headquarters) Upazila under Mymensingh district in Bangladesh. Data were collected on day-old chick weight (DOCW), live broiler weight at market age (MW), feed conversion ratio (FCR), average daily body weight gain (ADG), mortality up to age of marketing (MTRT) during June and July, 2014 using a pre-tested questionnaire by door-to-door visit. Seventeen out of 20 farms had broiler houses with gable type roof of corrugated iron sheet (CIS), all farmers were using rice husk as litter materials and electric brooder for brooding birds for 7 days. To minimize heat stress, 65% farmers used electric fan and drinking water, and to minimize cold stress quantities of litter materials were increased and vitamin C was supplied with lukewarm drinking water. Newcastle Disease (ND) and Infectious Bursal Disease (IBD) vaccines were used by all farmers. Mean ADG, MW, DOCW and MTRT were 45.3 ± 1.2g/bird, 1581.6 ± 46.1g/bird, 54.7 ± 3.0g/bird and 5.2 ± 1.0%, respectively. Feed from two different companies had no significant effect on FCR and MTRT but feed company affected the ADG significantly. DOCW, farm size and farmers education did not affect ADG, FCR and MTRT significantly.Bangl. vet. 2014. Vol. 31, No. 2, 84-90